Transcriptional regulation and therapeutic potential of cyclin-dependent kinase 9 (CDK9) in sarcoma - Walker, Robert L.; Hornicek, Francis J.; Duan, Zhenfeng (Biochemical pharmacology, 2024)
[Display omitted] Sarcomas include various subtypes comprising two significant groups – soft tissue and bone sarcomas. Although the survival rate for some sarcoma subtypes has improved over time, the current methods of treatment remain efficaciously limited, as recurrent, and metastatic diseases remain a major obstacle. There is a need for better options and therapeutic strategies in treating sarcoma. Cyclin dependent kinase 9 (CDK9) is a transcriptional kinase and has emerged as a promising target for treating various cancers. The aberrant expression and activation of CDK9 have been observed in several sarcoma subtypes, including rhabdomyosarcoma, synovial sarcoma, osteosarcoma, Ewing sarcoma, and chordoma. Enhanced CDK9 expression has also been correlated with poorer prognosis in sarcoma patients. As a master regulator of transcription, CDK9 promotes transcription elongation by phosphorylation and releasing RNA polymerase II (RNAPII) from its promoter proximal pause. Release of RNAPII from this pause induces transcription of critical genes in the tumor cell. Overexpression and activation of CDK9 have been observed to lead to the expression of oncogenes, including MYC and MCL-1, that aid sarcoma development and progression. Inhibition of CDK9 in sarcoma has been proven to reduce these oncogenes’ expression and decrease proliferation and growth in different sarcoma cells. Currently, there are several CDK9 inhibitors in preclinical and clinical investigations. This review aims to highlight the recent discovery and results on the transcriptional role and therapeutic potential of CDK9 in sarcoma.